PENGARUH PENAMBAHAN SERBUK KACA TERHADAP KUAT TEKAN BETON SELF COMPACTING CONCRETE - Sianipar, Naomi Frisda (2015)
Limbahkacadalamjumlahbesar yang berasaldariindustrimaupunrumahtanggamerupakansumbermasalahbagilingkungan. Salah satuusahauntukmengatasimasalahtersebutadalahdenganmemanfaatkanlimbahserbukkacasebagaipowderpadacampuranbetonself compacting concrete. Betoninimemilikikemampuanmengalir, mengisiruang, danmelewatihalangankerapatantulangan.Serbukkacadiharapkandapatmengisiruang yang kosongpadabeton.Bahantambahlainnya yang digunakanadalahsuperplasticizersebesar 1.5% dariberat semen.Metodeyang digunakanuntukmerancangkomposisicampuranbetonself compactingadalahmetode ACI (American Concrete Institute).Penelitianinidilakukanuntukmengetahuipengaruhpenambahanserbukkacaterhadapkuattekanbeton SCC.Pengujianbetonsegar yang dilakukanadalahslump flow test, segregation resistance test, danfilling ability test. Kemudiandilakukanujikuattekanpadausiabeton 3, 7, 14 dan 28 hari. Terdapatempatvariasicampuranserbukkaca yang ditambahkanyaitu 5%, 10%, 15%, dan 20% dariberat semen.Kuattekantertinggididapatdarikomposisibetondengancampuranserbukkacasebanyak 10% danhasilkuattekanpadausia 28 harimencapai55.36MPa.Sedangkanhasilkuattekanterendahdidapatdarikomposisibetondengancampuranserbukkacasebanyak 20%denganhasilkuattekanmencapai51.33 MPa.Untukmelengkapihasilpenelitian, dapatdilakukanpengujianslump losspadabetonsegarsertapengujiankuatgeserdanlenturpadabeton yang telahmengeras. Kata kunci :Serbukkaca, Self Compacting Concrete, Superplasticizer,Beton, Kuattekan. Waste glass in large number from industry and households is a source of problems for the environment. One solution to overcome this problem is to utilize waste glass powder as a powder in self compacting concrete. Self Compacting Concrete (SCC) is a concrete that can be solid by its own with the high slump, it is capable of filling the mold (formwork) without having segregation and reaching its highest density. Glass powder is expected to fill voids in the concrete. The other addition of admixture aresuperplasticizer. Superplasticizer that is used in this research is type ADVA 455 with constant dose for all variant as many as 1.5%. The methods used to design the composition of the self compacting concrete mix is American Concrete Institute method (ACI). This research is conducted to now the influence of the addition of glass powder on SCC compressive strength. The data are analysed by using slump flow test, segregation resistance test, filling ability test, and examining the strength of concrete tense of age 3, 7, 14, and 28 days. There are four variants of the mixture of glass powder addition, they are 5%, 10%, 15%, 20% of the cement weight. The addition of glass powder has influence on the increase of compressive strength. The highest strength of the test is obtained from concrete composition, with the mixture of glass powder as many as 10% and the compressive strength in age 28 reach 55.36Mpa. While the result of the lowest compressive strength is obtained from the concrete composition with silica fume addition as many as 20% and reaches 51.33Mpa. To complete the research result, slump loss test can be used on the fresh concrete and also shear strength and flexural strength test on the concrete that has been hard. Keyword : Glass powder, self compacting concrete, admixture, superplasticizer, compressive strength